The Role of Social Media to Eradicate Leprosy Stigma: Tertiary Prevention for Enhanced Lives - Diansasnita, Aisha; Azzahra, Alifia rizqyandra; Thohar, Amru ubaidillah; Arini, Dewi; Husna, Fahrun Nisa sifaul; Rahma , Fidela; Musyaffa, Hanif ahmad; Harianto, Maria kireina; Permatasari, Karina putri; Ummah, Mazroatul khoiroh; Testania, Nabila; Azzahro, Nur fauziah; Usraturrahmah, Usraturrahmah (Tarqabin Nusantara Group, 2024)
Leprosy is an infectious disease that can affect the skin, peripheral nerves and other organs in the human body. Leprosy is caused by the bacteria Mycobacterium leprae, which is also known as leprae. Even though leprosy has a long history, this disease is still a global health problem, especially in developing countries like Indonesia. The aim of this research is as a health promotion tool to provide information and education about leprosy by providing tertiary prevention efforts through social media with the Instagram account @komkes.ikmb22. The research method used was content analysis of health promotion media. This research shows that media in the form of posters regarding tertiary prevention of leprosy succeeded in attracting the attention of the public or viewers with positive interactions, namely by giving 61 likes and 2 comments. It can be concluded that health promotion through social media, especially Instagram, can be an effective strategy to increase public understanding about leprosy and reduce social stigma. Increasing knowledge regarding tertiary prevention of leprosy can change people's quality of life for the better.